Prevalence of cryptosporidiosis and hygiene practices among HIV/AIDS patients in southwest Uganda - Nakibirango J (Dove Medical Press, 2019)
Juliet Nakibirango, Vincent Mugenyi, Dickson Nsaba, Aron Nsimemukama, Simon Peter Rugera, Benson OkongoDepartment of Medical Laboratory Science, Faculty of Medicine, Mbarara University of Science and Technology, Mbarara, UgandaPurpose: To determine the prevalence of Cryptosporidium by age, sex, and duration on antiretroviral therapy (ART) and establish hygienic malpractices that may predispose to infection.Methods: We enrolled 138 HIV/AIDS patients on ART from June to October 2018. Stool samples were collected from study participants, wet saline preparations made and examined, stool samples concentrated using formal ether concentration, and smears stained using the modified Ziehl–Neelsen technique. Structured questionnaires were used to collect demographic data and hygienic malpractices that predisposed study participants to cryptosporidiosis infection.Results: Of 138, 99 (71.7%) were females and 39 (28.7%) males. The age range was 9–69 years and mean age 37 years. The overall prevalence of cryptosporidiosis was three (2.17%). The most affected age-groups were 31–40 years (3.85%) and 21–30 years (3.22%), and only females (3.03%) were affected. The distribution of cryptosporidiosis according to the duration spent on ART showed that those who had spent <1 year on ART were the most affected (11.1%), followed by those who had spent 1–5 years 1 (2.2%), while those patients on ART for 6-10 years were 1 (1.7%) and those on ART for more than 10 years were not affected. There was no significant association between cryptosporidiosis and sex (P=0.272), educational background (P=0.670), handwashing (P=0.853), drinking boiled water (P=0.818), duration on ART (P=0.263), occupation (P=0.836), and age (P=0.723).Conclusion: The prevalence reported in this study is low; however, it is still vital for clinicians to proceed to have cryptosporidiosis as the main differential in HIV/AIDS patients with gastrointestinal infections.Keywords: Cryptosporidium, HIV/AIDS, diarrhoea, prevalence, risk factors